PERSPECTIVE OF REHABILITATION FOR DRUG ABUSERS: A COMPARATIVE STUDY OF THE INDONESIAN AND THAILAND LEGAL SYSTEMS (International Journal of Cultural and Social Science, 2026)
This study examines the regulation and implementation of rehabilitation for narcotics abusers through a comparative analysis of the legal systems of Indonesia and Thailand. Narcotics abuse constitutes both a legal issue and a public health problem that requires a comprehensive and recovery-oriented approach. In Indonesia, Law Number 35 of 2009 on Narcotics provides for medical and social rehabilitation as mandatory measures for addicts and victims of narcotics abuse. However, in law enforcement practice, punitive approaches in the form of imprisonment remain more dominant than rehabilitation. In contrast, Thailand, through the Narcotic Addict Rehabilitation Act B.E. 2545, explicitly positions narcotics abusers as subjects who are required to undergo rehabilitation through a diversion mechanism from the criminal justice system. This study indicates that the implementation of rehabilitation in Indonesia continues to face normative and practical obstacles due to an ambivalent legal framework and inconsistent law enforcement, whereas Thailand demonstrates a more determinative, integrated, and public health-oriented rehabilitation model.